Optimizing the utilization of coal in Indonesia through downstreaming: Economic benefits, challenges and solutions - Rahman, Dudi; Raphael, Francis (Economic Military and Geographically Business Review, 2025)
Background: This study delves into the strategic optimization of coal resources in Indonesia through downstreaming, aiming to contribute to sustainable and value-driven utilization of the country's mineral wealth. The research highlights the benefits of downstreaming, including increased economic value and state revenues, while acknowledging the challenges such as environmental impacts and the need for advanced technologies. Methdos: This qualitative study analyzed coal utilization efficiency through downstream strategies, gathering insights from seven key informants in the coal sector. Data was collected via document analysis of EIA/ESIA reports, relevant regulations, and guidelines. A qualitative comparative analysis and descriptive methods were employed to identify patterns and challenges in coal beneficiation, focusing on stakeholders' views on the issue. Findings: The slow progress of coal downstreaming in Indonesia is attributed to financial constraints, technological complexity, and unclear regulations, despite government incentives. Strengthening collaboration between mining and energy production companies is key to improving coal utilization. Increased government support and commitment are needed to attract financial backing for downstream projects. Additionally, ongoing technical and economic studies on coal conversion for secondary and tertiary energy sources are essential to ensure energy availability, affordability, and sustainability.  Conclusion: The study emphasizes the importance of collaboration between mining companies, downstream companies, and the government, as well as the implementation of supportive regulations and incentives to encourage coal downstreaming. Overall, the study provides strategic recommendations for Indonesia to enhance the efficiency and responsible utilization of its coal resources through downstreaming. Novelty/Originality of this article: This study underscores the strategic importance of coal downstreaming in Indonesia, highlighting its economic potential, environmental challenges, and the need for collaboration and supportive policies to ensure sustainable resource utilization.